Sociodemographic and neurological profile of patients with spinal cord injury in a trauma hospital in Bangladesh - Mohiuddin, Md; Md. Monirul Islam; Rashid, Md. Imammur (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Not available